2018
DOI: 10.3390/s18041160
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Blood Pressure Estimation from ECG Using Machine Learning Techniques

Abstract: Background: Blood pressure (BP) measurements have been used widely in clinical and private environments. Recently, the use of ECG monitors has proliferated; however, they are not enabled with BP estimation. We have developed a method for BP estimation using only electrocardiogram (ECG) signals. Methods: Raw ECG data are filtered and segmented, and, following this, a complexity analysis is performed for feature extraction. Then, a machine-learning method is applied, combining a stacking-based classification mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(77 citation statements)
references
References 72 publications
(73 reference statements)
1
68
1
Order By: Relevance
“…Apart from the PTT-based BP estimation method, some other physiological features have been investigated to indicate BP changes, including PPG intensity ratio [109], Womersley number [110], radial electrical bioimpedance [111], modified normalized pulse volume [112], acceleration plethysmography (APG) [113], and diameter of a pulsating blood vessel [114]. Additionally, machine learning has also been applied to BP estimation to develop regression models between signal features and BP, and demonstrating promising estimation accuracy [115][116][117][118][119][120]. However, the interpretation of the datadriven model is nontrivial.…”
Section: B Continuous Blood Pressure Monitoringmentioning
confidence: 99%
“…Apart from the PTT-based BP estimation method, some other physiological features have been investigated to indicate BP changes, including PPG intensity ratio [109], Womersley number [110], radial electrical bioimpedance [111], modified normalized pulse volume [112], acceleration plethysmography (APG) [113], and diameter of a pulsating blood vessel [114]. Additionally, machine learning has also been applied to BP estimation to develop regression models between signal features and BP, and demonstrating promising estimation accuracy [115][116][117][118][119][120]. However, the interpretation of the datadriven model is nontrivial.…”
Section: B Continuous Blood Pressure Monitoringmentioning
confidence: 99%
“…Novel technologies have been developed that utilise ML techniques to measure heart rate and respiratory rate using only video, without any patient contact . ML has also been applied to cuff‐less BP monitoring using a single arm band, and to accurately predict BP using ECG recording …”
Section: Clinical Monitoringmentioning
confidence: 99%
“…28 ML has also been applied to cuff-less BP monitoring using a single arm band, and to accurately predict BP using ECG recording. 29,30 Clinical outcome predictions AI algorithms are becoming better at predicting the future, often outperforming current clinical scoring systems. Using raw data obtained from over 200 000 patients entire electronic medical records (over 46 billion data points), Rajkomar and Oren et al were able to predict in-hospital mortality with an area under the receiver operating characteristic curve of 0.93-0.94, validated across two sites.…”
Section: Clinical Monitoringmentioning
confidence: 99%
“…Other studies have shown that the ECG signal from Faros can also be used to calculate other variables such as BP [66], or to extract core body temperature with respect to clothing and persons' activity [67].…”
Section: Introductionmentioning
confidence: 99%